2017
DOI: 10.1021/acs.nanolett.7b02302
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nanoparticle Design in Determining Analytical Performance of Lateral Flow Immunoassays

Abstract: Rapid, simple, and cost-effective diagnostics are needed to improve healthcare at the point of care (POC). However, the most widely used POC diagnostic, the lateral flow immunoassay (LFA), is ~1000-times less sensitive and has a smaller analytical range than laboratory tests, requiring a confirmatory test to establish truly negative results. Here, a rational and systematic strategy is used to design the LFA contrast label (i.e., gold nanoparticles) to improve the analytical sensitivity, analytical detection ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 37 publications
3
164
0
Order By: Relevance
“…As smaller Pd−Ir NPs have lower k cat but similar k cat‐specific values compared to larger ones (Figure ), we assume the enhanced detection sensitivities of smaller Pd−Ir NPs based ELISAs can be ascribed to the capture of a great larger number of Pd−Ir NPs during the detection. This assumption is consistent with previous reports that smaller NPs have greater diffusivities and reduced steric effect that make them easier to bind to analytes through the antibody‐antigen interaction …”
Section: Figuresupporting
confidence: 93%
“…As smaller Pd−Ir NPs have lower k cat but similar k cat‐specific values compared to larger ones (Figure ), we assume the enhanced detection sensitivities of smaller Pd−Ir NPs based ELISAs can be ascribed to the capture of a great larger number of Pd−Ir NPs during the detection. This assumption is consistent with previous reports that smaller NPs have greater diffusivities and reduced steric effect that make them easier to bind to analytes through the antibody‐antigen interaction …”
Section: Figuresupporting
confidence: 93%
“…Although RDTs have dominated point-of-care-tests (POCT) for malaria, there have been major concerns about the stability and performance relating to sensitivity and specificity which constrains their impact [25][26][27]. Currently, the commercially available RDTs are about 1000-fold lower in sensitivity than alternative laboratory-based techniques [28][29][30], thus they do not provide the sensitivity and quantitation comparable to the gold-standard microscopy or PCR [29]. Studies have reported that RDTs which incorporate pan-aldolase have poor sensitivity due to low expression of the enzyme by parasites.…”
Section: Parasite Development In Humans Biomarkers and Diagnosismentioning
confidence: 99%
“…To improve the analytical sensitivity and detection range of the Au NP-based LFA, Bischof et al investigated the effect of different size of Au NPs (30, 60, and 100 nm) on the performance of LFA devices [186]. They found that the sensitivity was significantly dependent on the optical properties of Au NPs and their binding efficiency.…”
Section: Plasmonic Paper Devicesmentioning
confidence: 99%